Quantitative analysis of ecological networks - Dale, Mark R. T. 1951-; Fortin, Marie-Josée 1958- (Cambridge University Press, 2021)
Network thinking and network analysis are rapidly expanding features of ecological research. Network analysis of ecological systems include representations and modelling of the interactions in an ecosystem, in which species or factors are joined by pairwise connections. This book provides an overview of ecological network analysis including generating processes, the relationship between structure and dynamic function, and statistics and models for these networks. Starting with a general introduction to the composition of networks and their characteristics, it includes details on such topics as measures of network complexity, applications of spectral graph theory, how best to include indirect species interactions, and multilayer, multiplex and multilevel networks. Graduate students and researchers who want to develop and understand ecological networks in their research will find this volume inspiring and helpful. Detailed guidance to those already working in network ecology but looking for advice is also included
Title from publisher's bibliographic system (viewed on 22 Feb 2021)
Keywords: Ecology / Statistical methods; Quantitative research; System analysis; Statistik; Ökologie; Methode; Quantitative Analyse